Representation of Social Inequality in Russia in the Movie Холоп (Son of a Rich) by Klim Shipenko - Matahati, Aura Pijar; Aviandy, Mochamad; Rahmi, Rahmi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2025)
Social inequality has been a persistent issue in Russia across the 19th and 21st centuries, manifesting in different forms depending on historical, cultural, and political contexts. This study examines the representation of social inequality in Klim Shipenko’s 2019 film Холоп (Son of a Rich), focusing on how visual and linguistic elements encode and communicate this theme. Employing Stuart Hall’s qualitative representation analysis, the research explores the encoding and decoding of signs that highlight social disparity. The findings classify representations of inequality into three key dimensions: social class, social status, and power dynamics, drawing upon Max Weber’s theoretical framework. The study reveals how the film portrays systemic social hierarchies, emphasizing disparities between nobility and serfs in the 19th century and between urban elites and the rural lower class in the 21st century. Additionally, it examines how power structures perpetuate oppression through autocratic rule in the past and oligarchic influence in the present. By critically analyzing the film’s depiction of social conflicts, discrimination, and authority imbalances, this study underscores its role in delivering social commentary. The film functions as a medium of critique, shaping viewers’ perceptions of Russia’s socio-political realities. Ultimately, this research contributes to broader discussions on social inequality and media’s role in reflecting and challenging entrenched power structures.